Dive in the “Soul” of Corporate Social Responsibility Through the Philosophy of Tri Hita Karana - Cahyaningtyas, Fadilla; Salleh, Saluana Che (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 1 (2024), 2024)
This study employs a qualitative research methodology to examine Corporate Social Responsibility (CSR) practices within the "Triple Bottom Line" framework, interpreted through the lens of "Tri Hita Karana." Utilizing secondary data from 2018 to 2023, the research finds that CSR aligns with Tri Hita Karana's core principles: Parhyangan (Connection with the Divine), Pawongan (Interpersonal Connections), and Palemahan (Harmony with Nature). Parhyangan manifests in spiritual engagement activities, including constructing worship facilities, Pawongan in initiatives benefiting local communities, and Palemahan in environmental conservation efforts. The study asserts that CSR, embodying the "Triple Bottom Line," balances profit, people, and the planet. Integrating Tri Hita Karana principles fosters positive stakeholder interactions, emphasizing CSR's potential to enhance community well-being, environmental sustainability, and economic objectives simultaneously. Keywords:  Corporate Social Responsibility, Tripple Bottom Line, Tr ita Karana, Parhyangan, Pawongan, Palemahan